Innovative Batik Motif Designs for the Sekolah Indonesia Makkah(SIM) Dress Code as Cultural Symbol of Pride for Diaspora Students - Ponimin Ponimin (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2025)
Fostering a sense of love for Indonesia is essential for every citizen, including students of Sekolah Indonesia Makkah who live in Saudi Arabia. This can be achieved with their iconic school uniforms featuring batik decorative motifs that reflect Indonesian aesthetics combined with iconic elements of the local culture and natural environment of Mecca, Saudi Arabia. School uniforms featuring such batik ornaments can also instill a sense of pride among students as members of the Indonesian nation living abroad, particularly in Saudi Arabia. To produce a dress code design featuring these motifs, a creative art-based method is required. The process involves: (a) developing conceptual designs, (b) creating design sketches for batik motifs, (c) applying the designed motifs to textile materials, (d) sewing prototype products, and (e) analyzing the aesthetic outcomes of the dress code that incorporates Indonesian and Saudi Arabian decorative elements. The creative outcome of this research is a prototype of a school dress code design that features decorative motifs inspired by the natural and cultural elements of both Indonesia and Saudi Arabia, developed for three education levels: elementary school, junior high school, and senior high school.